Gender Quota and Women’s Needs in Urban Planning Practices by Local Councils: The Case of Ramallah Governorate in Palestine - Manal Al-Bishawi; Faten Timraz (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The aim of this study is to investigate the relationship between gender quota and women’s needs in urban planning practices by local councils in Palestine which is considered to be a developed country, with a particular attention to Ramallah governorate. Most of the existing studies concerning this topic focus on the importance of gender quota in providing access for women to decision making process without considering well enough the role of gender quota in women’s effective participation in fulfillment of their needs and how this influences sustainability of the urban environment. Observations and interviews are used as two main methods. The result of this study showed that although gender quota supports women's access to decision-making process, it is not enough to guarantee the fulfillment of their needs, which restricted their use of the urban environment. Women’s awareness of their needs in addition to other obstacles, should be considered for the effectiveness of gender quota.